2004
DOI: 10.1016/j.jhsb.2003.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Pain Associated with Local Anaesthetic Infiltration for open Carpal Tunnel Decompression

Abstract: This prospective, randomized study assessed the effectiveness of buffering lidocaine with sodium bicarbonate for reducing the pain associated with local anaesthetic infiltration for open carpal tunnel decompression. Twenty-one patients undergoing bilateral open carpal tunnel decompression received, in a randomized manner, lidocaine 1% with adrenaline (1:200,000) in one hand and the same local anaesthetic buffered with 8.4% NaHCO3 at a 5:1 ratio in the other hand. Pain, especially its burning element, was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 13 publications
0
16
2
Order By: Relevance
“…The mean pain scores at this stage in the procedure were 3.2 and 3.3 with the modified Gale and the modified Altissimi and Mancini techniques, respectively. These were much lower than the pain scores described by Vossinakis et al (2004) with infiltration of unbuffered lignocaine. This could be because of the smaller volume of the anaesthetic used in our series (5 ml as compared to 15 ml in the study by Vossinakis et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The mean pain scores at this stage in the procedure were 3.2 and 3.3 with the modified Gale and the modified Altissimi and Mancini techniques, respectively. These were much lower than the pain scores described by Vossinakis et al (2004) with infiltration of unbuffered lignocaine. This could be because of the smaller volume of the anaesthetic used in our series (5 ml as compared to 15 ml in the study by Vossinakis et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
“…These were much lower than the pain scores described by Vossinakis et al (2004) with infiltration of unbuffered lignocaine. This could be because of the smaller volume of the anaesthetic used in our series (5 ml as compared to 15 ml in the study by Vossinakis et al, 2004). We also injected the local anaesthetic slowly, which could also have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 57%
“…Three studies have looked at the effect of buffering acidic local anaesthetic solution to physiological pH prior to injection. Two showed some benefit (Vossinakis et al, 2004;Yiannakopoulos, 2004) and the third showed no pain reduction (Watts et al, 2004). Palmon et al (1998), in a study of healthy volunteers, randomized patients to injections with plain or buffered lidocaine using either a 25-gauge needle or a 30-gauge needle.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in pain at the site of injection, obtained through the addition of bicarbonate to lidocaine or mepivacaine, has been demonstrated in several clinical trials where local anaesthetics were given as cutaneous infiltration, including the treatment of traumatic wound lacerations [9], anaesthesia for digital nerve block [10], skin infiltration and intravenous catheterization prior to surgery [11], surgery for correction of prominent ears [12], repair surgery for combined upper eyelid blepharoplasty and levator advancement ptosis [13], carpal tunnel surgery [14, 15], and ambulatory phlebectomy procedures, the latter study testing specifically the association between mepivacaine and bicarbonate [16]. Overall, these studies were randomized controlled trials comparing a control group receiving the local anaesthetic given alone versus the group receiving the anaesthetic in a bicarbonate vehicle, and pain scores were obtained through visual analogic scales.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%